PENGARUH JUDI ONLINE TERHADAP KETAHANAN KELUARGA DALAM PERSPEKTIF SADDU DZARI’AH - Apifah Delisa; Fuad Rahman, Siti Marlina, Madyan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to analyze online gambling and its relevance to family resilience in Jambi city. Researchers used qualitative research through an empirical juridical approach. Data were obtained through direct observation, interviews with Judges, Mediators and Registrars, and analysis of related documents. The results of this study indicate that there is a relationship between online gambling cases and the damage to family resilience which leads to divorce cases in Jambi City. Family resilience includes physical, economic, psychological, and socio- cultural resilience, although the most significant impact of online gambling on family resilience is financial problems such as economic difficulties because generally online gambling players are lazy to work because they are immersed in online gambling games on their cellphones, if they are addicted, they do not hesitate to sell existing property to threaten their own families. The legal provisions of online gambling can be seen from the perspective of Saddu Dzari'ah, in order to minimize and even close the opportunity to play online gambling, of course anticipatory and preventive steps such as; regulation, education, economic empowerment, and synergy between institutions need to be carried out, with the commitment and cooperation of all parties, it is hoped that Jambi City will be free from online gambling traps and build a more moral and prosperous future.